Unveiling the nation : the politics of secularism in France and Quebec - Laxer, Emily, 1983- (McGill-Queen's University Press, 2019)
"Over the last few decades, politicians in Europe and North America have fiercely debated the effects of a growing Muslim minority on their respective national identities. In some countries, these debates have produced laws that prohibit certain Islamic religious coverings in public spaces and institutions. In others, legal restriction remains subject to intense political conflict. Social scientists seeking to understand these differences have placed significant emphasis on countries' historically-rooted 'models' of nationhood and their attendant discourses of secularism. Emily Laxer's Unveiling the Nation problematizes this approach. Using France and Québec as illustrative cases, it traces how the struggle among political parties for power and legitimacy shapes states' responses to Islamic signs. Based on historical evidence and behind-the-scenes interviews with politicians and activists, Laxer uncovers unseen linkages between structures of partisan conflict and the strategies that political actors employ when articulating the secular boundaries of the nation. In France's historically classed-based political system, she argues, left and right parties have converged around a restrictive secular agenda in order to limit the siphoning of votes by the ultra-right. In Québec, by contrast, the longstanding electoral salience of the 'national question' has encouraged political actors to project highly conflicting images of the province's secular past, present, and future. Coming at a moment of heightened debate in the global politics of religious diversity, Laxer's Unveiling the Nation sheds critical light on the way party politics, and its related instabilities, shapes the secular boundaries of nationhood in diverse societies."--